2015
DOI: 10.1016/j.humov.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory integration in children with Developmental Coordination Disorder

Abstract: 1This study examines how multisensory stimuli affect the performance of children with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…There were three studies under this category using very different paradigms, two of good quality (Table SXII): bimodal stimuli (i.e. object location specified by visual and auditory cuing) was shown to improve motor planning of aiming movements in DCD but not controls; a another study showed a negligible relationship between sensory integration ability and everyday functional skills; the third showed that children with DCD were capable of making multisensory visual‐to‐motor adaptations in response to a visual feedback rotation …”
Section: Resultsmentioning
confidence: 99%
“…There were three studies under this category using very different paradigms, two of good quality (Table SXII): bimodal stimuli (i.e. object location specified by visual and auditory cuing) was shown to improve motor planning of aiming movements in DCD but not controls; a another study showed a negligible relationship between sensory integration ability and everyday functional skills; the third showed that children with DCD were capable of making multisensory visual‐to‐motor adaptations in response to a visual feedback rotation …”
Section: Resultsmentioning
confidence: 99%
“…Reaction time (RT) tasks have also been used as an indicator of auditory-motor processes [65][66][67]. For example, RT was measured to assess how auditory stimuli influence the performance in an aiming task (i.e., moving a finger from the start position to the target button) as part of a multisensory paradigm [67].…”
Section: Reaction Timementioning
confidence: 99%
“…Research shows that children with DCD exhibit slower, more variable reaction times compared to typically developing children as a result of either slower processing speed, inefficient preparation of movement or both [15]. Motor planning appears to be impaired in DCD on most but not all tasks.…”
Section: Dcd Motor Skillsmentioning
confidence: 99%
“…Tests of visuomotor adaptation have shown that children with DCD present a lower capacity to adapt their movement to different task constraints. This has been shown by a higher movement variability, lower movement accuracy and/or longer movement durations [15]. Movement times or durations are frequently reported to be longer in children with DCD than in typically developing children, probably as a result of a stronger reliance on visual information for movement control [20].…”
Section: Dcd Motor Skillsmentioning
confidence: 99%
See 1 more Smart Citation